Anaesthesia education in Nepal - What residents think - Shrestha, Anil (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Education in Anesthesiology is one of the growing fields of medical education in Nepal. The feedback and constructive suggestions from the Anesthesiology residents regarding their training program is essential for the improvement of the training program. Methods: This prospective questionnaire based study was done at five different medical institutions of Nepal where postgraduate training in Anesthesiology is available. Questionnaire consisting of several questions related to anesthesia training were distributed to 45 anesthesiology residents of different institutions and were asked to fill and return to the investigator. Results: Out of 45 questionnaires 38 responded. Only 50% of the respondents said that classes were regular in their institution. Only 23.68% of the residents were satisfied with the exam system. More than two third (76.32%) felt that their undergraduate education in anesthesiology was inadequate. Majority of the residents think that the education in anesthesiology in Nepal is at par or better than education in other subjects and 81.58% think that it is becoming better than before. Half of the residents feel that the facilities provided to them is better considering the national condition. Sixty-six percent of the residents think that the future of anesthesia in Nepal is bright. Conclusion: Majority of the residents think that the anesthesia education in undergraduate level is inadequate and developing anesthesia as a separate subject may attract more students to join anesthesiology. Most of the residents are satisfied with the improvement in education in anesthesia and its future but feel that there are lot more to do. Journal of Society of Anesthesiologists 2014 1(2): 65-69